THE INFLUENCE OF USING CHORAL READING TECHNIQUE TO THE ELEVENTH GRADE STUDENTS’ READING MASTERY AT SMA NEGERI 1KASIMBAR - aldi, andi; Muhammad Ihsan; Fitriningsih; Rasmi (Datokarama English Education Journal, 2021)
This paper focuses on the using of choral reading technique to the eleventh grade students’ reading mastery at SMA Negeri 1 Kasimbar. The writer applied quasi experimental research design and need pre-test and post-test to both experimental and control class. The pre-test was to know the level of students’ reading mastery ability before giving treatment while the post-test was used to know the result after giving treatment. There was a significant difference score of the post-test of the experimental class (1.495) and the control class (1.235). The level of significance was set up 0,05 with 40 degree of freedom ( (df) = Nx + Ny = 21 + 21 + 40). The result of data analysis indicates that tcounted (3,729) which was higher than ttable, it means that the hypothesis of the research was accepted. Thus, there was significant influence of using choral reading technique to the eleventh grade students at SMA Negeri 1 Kasimbar.